PERCEPTION OF SPEECH USING AUDIO VISUAL AND REPLICA FOR STUDENTS OF SULTAN AGENG TIRTAYASA UNIVERSITY - Ediwarman Ediwarman; Syafrizal Syafrizal; John Pahamzah (Universitas Islam Sumatera Utara, 2021)
This paper exmined the perception of speech using audio visual and replica for students of Sultan Ageng Tirtayasa Univesity. This research was aimed at discussing face-to-face conversation or speech felt by the ears and eyes. The prerequisites for audio-visual perception of speech by using ambiguous perceptual sine wave replicas of natural speech as auditory stimuli are studied in details. When the subjects were unaware that auditory stimuli were speech, they only showed a negligible integration of auditory and visual stimuli. The same subjects learn to feel the same auditory stimuli as speech; they integrate auditory and visual stimuli in the same way as natural speech. These research result suggests a special mode of perception of multisensory speech.